Kingdom of the Wicked - Maniscalco, Kerri (Patterson, James. Kingdom of the Wicked, 2020)
Emilia and her twin sister Vittoria are streghe - witches who live secretly among humans, avoiding notice and persecution. One night, Vittoria misses dinner service at the family's renowned Sicilian restaurant. Emilia soon finds the body of her beloved twin ... desecrated beyond belief. Devastated, Emilia sets out to find her sister's killer and to seek vengeance at any cost - even if it means using dark magic that's been long forbidden.